The Economics of Cryptocurrencies - Bitcoin and Beyond - Jonathan Chiu; Thorsten Koeppl (Queen's University, Department of Economics, 2017)
How well can a cryptocurrency serve as a means of payment? We study the optimal design of cryptocurrencies and assess quantitatively how well such currencies can support bilateral trade. The challenge for cryptocurrencies is to overcome double-spending by relying on competition to update the blockchain (costly mining) and by delaying settlement. We estimate that the current Bitcoin scheme generates a large welfare loss of 1.4% of consumption. This welfare loss can be lowered substantially to 0.08% by adopting an optimal design that reduces mining and relies exclusively on money growth rather than transaction fees to finance mining rewards. We also point out that cryptocurrencies can potentially challenge retail payment systems provided scaling limitations can be addressed.
Keywords: E4; E5; L5; 330; Cryptocurrency; Blockchain; Bitcoin; Double Spending; Payment Systems